Diversity of Deep-Sea Echinoderms From Costa Rica - Alvarado, Juan José; Chacón-Monge, José Leonardo; Azofeifa-Solano, Juan Carlos; Cortés, Jorge (Frontiers in Marine Science, 2022)
Echinoderms are a highly diverse group and one of the most conspicuous in the deep sea, playing ecological key roles. We present a review about the history of expeditions and studies on deep-sea echinoderms in Costa Rica, including an updated list of species. We used literature and information gathered from the databases of the California Academy of Sciences, the Benthic Invertebrate Collection of the Scripps Institution of Oceanography, the National Museum of Natural History, the Museum of Comparative Zoology and the Museo de Zoología from the Universidad de Costa Rica. A total of 124 taxa (75 confirmed species) have been collected from the Costa Rican deep sea, 112 found in the Pacific Ocean, 13 in the Caribbean Sea, and one species shared between the two basins. We report 22 new records for the Eastern Tropical Pacific, 46 for Central American waters, and 58 for Costa Rica. The most specious group was Ophiuroidea with 37 taxa, followed by Holothuroidea (34 taxa), Asteroidea (23 taxa), Echinoidea (17 taxa), and Crinoidea (11 taxa). The highest number of species (64) was found between 800 m and 1200 m depth. Only two species were found deeper than 3200 m. Further efforts on identification will be required for a better comprehension of the diversity of deep-sea echinoderms. Limited research has been done regarding the biology and ecology of deep-sea echinoderms in Costa Rica, so additional approaches will be necessary to understand their ecological functions.